Studi Terhadap Proses Reformasi Birokrasi Di Pemprov Banten Dan Pemprov Jawa Barat - Prayitno, Budi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
Bureaucratic reform is one of the government programs that are projected to improve the performance of services to the community. Suck we all know, the public demand for the bureaucracy that serves the expectations of many parties. So far, the focus of bureaucratic reforms directed to government agencies at the central level. Subsequently, in 2013, in addition to government institutions at the central level, some regions consist of provinces, districts, and the city also became a pilot project under the supervision of bureaucratic reforms Ministry of Administrative Reform and Bureaucratic Reform. A pilot project areas bureaucratic reform policy is Jabar Banten provincial government and the provincial government. The results showed that the challenges faced by local governments are quite varied. There are many factors that cause this, factors such as leadership, bureaucratic mindset, and regional characteristics.